Effect Of Return On Equity, Current Ratio, And Debt To Equity Ratio On Stock Prices - Auliareina, Sahda Syahira; Putri, Intan Lifinda Ayuning (Telaah Ilmiah Akuntansi dan Perpajakan, 2026)
The objective of this quantitative research is to assess the influence of return on equity, current ratio, and debt-to-equity ratio on stock prices. The data were acquired from a sample of thirteen IDX30 companies listed on the Indonesia Stock Exchange during the 2018-2022 period. Analysis and hypothesis testing were performed through panel data regression in EViews 12. This study finds that return on equity and current ratio have no effect on stock prices, while debt-to-equity ratio has a negative effect on stock prices. This finding reinforces the signaling theory, which explains that the higher the ratio between debt and equity, the greater the financial risk, and it can be interpreted as a strong negative signal for investors. This negative signal is then reflected in lower stock prices. Therefore, IDX30 companies need to prioritize balanced capital structure to attract investors’ attention and increase stock value. This finding also contributes to the literature on factors influencing stock prices in Indonesia.